Marketing Paradigms for Rural India - Thomas, Thomas T. (Indian Journal of Marketing, 2012)
Rural India is still a mystery, with perspectives varying with the researchers. The large share of population residing in these areas with diverse cultures, aspirations and needs make it a challenging proposition for both academics and industrialists. But this has not taken the charm off this fast evolving market. Marketers have already made inroads into rural India with their diverse offers. While the going was tough earlier, the recent revolution in technology and communication has made rural India more accessible though at the same time, more discerning and, therefore, more distant in terms of approachability and targeting. The once successful marketing strategies need to be re-tuned to suit the new requirements. Earlier paradigms in marketing need a changed focus so as to make a genuine entry and ensure long-term survival. This paper looks at the scenario and explores opportunities for the corporates to take advantage of a market that holds almost three-fourths of all Indians.